Revisiting The Mindfulness Framework In Heritage Tourism - Tan, Poh Ling (2017)
It has been propounded that mindful tourists are able to appreciate and act responsibly at heritage sites, as compared to tourists who are mindless. The mindfulness framework suggested by Moscardo (1996, 1999) has been acknowledged as important, however, there are few gaps in the application: lack of explanation on Visitor Factor in influencing mindfulness and lack of specific measure of mindfulness and interpretive outcome in tourism context. The overall research objective of this study is to enhance the mindfulness framework in explaining tourist interpretative outcome. This research examine the influence of Visitor Factors and Communication Factors on mindfulness. This research is conducted in Penang, a destination listed under the UNESCO World Heritage